Intertextual Strategy of the Narrator of the Second Epistle of Peter in the Catalogue of Virtues (1:5-7) - Rosik, Mariusz; Wojciechowska, Kalina (Verbum Vitae, 2021)
The Second Epistle of Peter is one of the least studied texts of the New Testament. It is usually compared with 1 Peter and/or Jude and indeed shows some similarities and some differences with these texts. But little attention is paid to the originality of 2 Peter both in its interpretation of texts from the Jewish tradition and in the application of intertextual strategies to elements of Greek philosophy. 2 Pet 1:5-7 is undoubtedly one of the most Hellenized passages of the epistle. Not only did the narrator use a hierarchical catalog of virtues popular in Greek literature, but also terms that are commonly associated with ethics, especially the stoic ethics (faith – πίστις; virtue – ἀρετή; knowledge – γνῶσις). This article aims to present the manner in which the narrator in 2 Pet 1:5-7 enters into dialogue with Greek ethical texts and how he transforms, innovates, and reinterprets these texts. In other words, what intertextual strategy he uses.